Revitalisasi Gotong Royong sebagai Upaya Membangun Solidaritas Melalui Peringatan Hari Kemerdekaan - Nurhalimah, Siti; Samsuri, Mahmud; Muthi'Uddin, Ahmad (Insan Kreasi Media, 2025)
The Independent Community Service Program (KKN) conducted in Kaduronyok Village, Bukit Kemuning, North Lampung, aimed to revive the value of cooperation (gotong royong) to strengthen the community's dwindling social solidarity. This goal was realized through activities such as parades, Independence Day competitions, and village decorations designed to foster a spirit of togetherness and strengthen the value of unity. The method used was a participatory approach involving all levels of society from the planning stage to the implementation of activities. This method was chosen to foster a sense of responsibility and direct involvement in the program's success. The results of the activities demonstrated increased community enthusiasm, re-established intergenerational cooperation, and the creation of a harmonious atmosphere that strengthened national values and promoted religious moderation. Thus, this Independent KKN effectively became a means for enhancing cooperation while maintaining unity and integrity in the community's social life.